Constitutive modeling of randomly oriented electrospun nanofibrous membranes - Wong, Dannee; Verron, Erwan; Andriyana, Andri; Ang, Bee Chin (Springer Verlag, 2019)
In this paper, a simple phenomenological model describing the macroscopic mechanical response of electrospun nanofibrous structures is proposed. Motivated by the experimental observation, the model development starts from the description of membrane response at fiber scale in order to capture individual fiber response and irreversible inter-fiber interactions using hyperelastic and large strain elasto-plastic frameworks, respectively. The macroscopic response is subsequently obtained by integrating the fiber responses in all possible fiber orientations. The efficiency of the proposed model is assessed using experimental data of PVDF electrospun nanofibrous membranes. It is found that the model is qualitatively in good agreement with uniaxial monotonic and cyclic tensile loading tests. Two other deformation modes, i.e., equibiaxial extension and pure shear (planar extension), are simulated to further evaluate the model responses. Finally, the deformation-induced fiber re-orientation is investigated for different modes of deformations. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.